The influence of hydrogen on cyclic plasticity of <001> oriented nickel single crystal. Part I: Dislocation organisations and internal stresses. (March 2020) - Hachet, G.; Oudriss, A.; Barnoush, A.; Milet, R.; Wan, D.; Metsue, A.; Feaugas, X.
Abstract: The present paper discussed the impact of hydrogen on the mechanical response of cyclically strained nickel single crystal oriented for multi-slips at different length scales. At macroscale, hydrogen seems to induce competition between softening and hardening of the metal as a function of the plastic strain amplitude. Then, by separating internal stresses induced by long-range and short-range interactions between dislocations (represented by back and effective stresses, respectively), we noted that hydrogen reduces the effective stress but has a more complex behaviour with the back stress. Therefore, observations with transmission electron microscope and nano-indentation tests have been performed on cyclically pre-strained nickel single crystal with and without hydrogen. The dislocation organisation induced by the cyclic tests is similar for nickel with and without hydrogen. In both cases, the dislocation arrangement can be affiliated to a composite structure with a wall phase containing mainly edge dislocation dipoles and a channel phase where the mobility and cross-slip events of screw dislocations occurred. From both approaches, we observed that hydrogen hardens the wall phase while it softens the channel phase. These results are discussed on the base of plasticity mechanisms. Highlights: The consequences of hydrogen on the cyclic hardening of nickel single crystal oriented for multi-slips have been determined. Hydrogen softens nickel single crystal at hardening stage II0 and III0 and induced a moderate hardening at stage III. The dislocation structure induced by cyclic tests can be affiliated to a composite structure composed of wall and channel phases for both nickel and nickel-hydrogen systems. From both transmission electron microscopy and nano-indentation tests, it is demonstrated that hydrogen hardens wall phase while it softens channel phase. Both effects are discussed in relation with plasticity process.